Are Slope Streaks Indicative of Global‐Scale Aqueous Processes on Contemporary Mars?. (9th January 2019) - Bhardwaj, Anshuman; Sam, Lydia; Martín‐Torres, F. Javier; Zorzano, María‐Paz
Abstract: Slope streaks are prevalent and intriguing dark albedo surface features on contemporary Mars. Slope streaks are readily observed in the equatorial and subequatorial dusty regolith regions with low thermal inertia. They gradually fade over decadal timescales. The proposed mechanisms for their formation vary widely based on several physicochemical and geomorphological explanations. The scientific community is divided in proposing both dry and wet mechanisms for the formation of slope streaks. Here we perform a systematic evaluation of the literature for these wet and dry mechanisms. We discuss the probable constraints on the various proposed mechanisms and provide perspectives on the plausible process driving global‐scale slope streak formation on contemporary Mars. Although per our understanding, a thorough consideration of the global distribution of slope streaks, their morphology and topography, flow characteristics, physicochemical and atmospheric coincidences, and terrestrial analogies weighs more in favor of several wet mechanisms, we acknowledge that such wet mechanisms cannot explain all the reported morphological and terrain variations of slope streaks. Thus, we suggest that explanations considering both dry and wet processes can more holistically describe all the observed morphological variations among slope streaks. We further acknowledge the constraints on the resolutions of remote sensing data and on our understanding of the Martian mineralogy, climate, and atmosphere and recommend continuous investigations in this direction using future remote sensing acquisitions and simulations. In this regard, finding more wet and dry terrestrial analogs for Martian slope streaks and studying them at high spatiotemporal resolutions can greatly improve our understanding. Plain Language Summary: Slope streaks are prevalent surface features on contemporary Mars. They have dark albedo and are abundant in the equatorial and subequatorial latitudes. The exact mechanisms behind their formation and development are still unknown, and several hypotheses have been proposed based on the physicochemical and geomorphological properties of slope streaks. These features generate a common interest because several hypotheses have linked them with transiently flowing liquid water on the Martian surface. Such probable linkages with Martian liquid water can have wide implications for understanding habitability conditions and ongoing water cycles on Mars and for evolving planetary protection policies to prevent possible contamination of Martian surface during future missions. Therefore, here we perform a systematic evaluation of the literature covering morphological and flow characteristics of slope streaks for water‐driven or dry dust avalanche mechanisms. We discuss the probable limitations of the various proposed models for slope streak development and provide perspectives on the plausible processes driving global‐scale slope streak formations on Mars. Continuously improving satellite and rover observations of Martian surface, topography, climate, and minerals are bound to improve our understanding of slope streaks in the coming years. Key Points: We provide a systematic survey and evaluation of the literature covering morphological characteristics of slope streaks We present a novel analog environment, Salar de Uyuni in the Bolivian Altiplano, where slope streaks are formed solely by deliquescence We offer perspectives on the probable mechanisms driving global‐scale slope streak formation on contemporary Mars